Mengukur korelasi Pembagian Kerja, Lingkungan Kerja dan Kinerja Pegawai - Abd Razak, Ikhsan (BJRM (Bongaya Journal For Research in Management), 2024)
The purpose of this study was to determine whether the division of labor and work environment partially and simultaneously have a positive and significant effect on employee performance at the Communication, Informatics, Statistics and Cryptography Service of Banggai Regency and to determine which has a dominant influence between the variables of Division of Labor and work environment on employee performance at the Communication, Informatics, Statistics and Cryptography Service of Banggai Regency. Based on the results of the study, it was obtained that partially the results of the study showed that partially the division of labor variable (X1) has a positive but insignificant effect on employee performance (Y) at the Communication, Informatics, Statistics and Cryptography Service of Banggai Regency. The results of the study showed that partially the work environment variable (X2) has a positive and significant effect on employee performance (Y) at the Communication, Informatics, Statistics and Cryptography Service of Banggai Regency. The work environment variable (X2) has a dominant and significant effect on employee performance (Y) at the National Unity and Politics Agency of Banggai Islands Regency. From the results of the ANOVA (analysis of variance) test or F test, the F-count is greater than the F-table, this means that there is a simultaneous influence between the variables of division of labor (X1) and work environment (X2) on employee performance (Y) at the Communication, Informatics, Statistics and Cryptography Service of Banggai Regency.